2017
DOI: 10.12669/pjms.332.12139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, predictors and triggers of migraine headache among medical students and interns in King Abdulaziz University, Jeddah, Saudi Arabia

Abstract: Objectives:To determine the prevalence, predictors, triggers and educational outcome of migraine among medical students and interns in King Abdulaziz University, Jeddah, Saudi Arabia.Methods:A cross-sectional study was completed among 566 participants selected through a multistage stratified random sample method. A validated, confidential, self-administered data collection sheet was utilized. It contained ID Migraine test™, Numeric Pain Rating Scale (NPRS). Questions about possible predictors, triggers and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
84
5
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(115 citation statements)
references
References 34 publications
(54 reference statements)
21
84
5
5
Order By: Relevance
“…The study focused on comorbidity between depression and anxiety and led to a positive correlation ( P < 0.001). [ 45 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study focused on comorbidity between depression and anxiety and led to a positive correlation ( P < 0.001). [ 45 ]…”
Section: Resultsmentioning
confidence: 99%
“…[ 46 ] Two studies showed that low academic performance students are more likely to develop depression. [ 34 45 ] Alakhtar et al . showed that GPA indicated a higher rate of depression among students with high and low GPA while having an intermediate GPA had lower rates.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of high prevalence of IBS among medical students may be attributed to their special learning environment (innumerable exams, profound clinical hospital practice, together with lacking the ability of self-adjustment and adaptation) (5,24). Enormous study and exams loads, increasing future job competition, undesirable living, and eating habits make medical students to be a particularly high-risk population for IBS (2,3,5).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study from Belgium reported an increased risk of patients with psychological co-morbidity to develop postinfectious IBS (PI-IBS) (34). Medical students represent a unique stress-heavy lifestyle model, consisting of long hours of focused physical and cognitive activity under significant social-competitive pressure (3,24).…”
Section:  Psychological and Psychiatric Factors (Stress Anxiety Anmentioning
confidence: 99%
“…A Saudi study on migraineurs from medical students and interns in King Abdulaziz University, Jeddah, Kingdom of SAudi Arabia, revealed a high rate of negative impact on educational performance )83.9%( and the ability to attend educational classes )78.2%(. 28 Limitations. To exclude secondary causes of headache, a complete history, physical examination, and appropriate investigations are needed in some cases, none of which was carried out in this study.…”
mentioning
confidence: 99%